Non-Visibility Within Adult Education: Reading What Lies Written and Breathing Beneath - Steven E. Noble (Adult Education Research Conference, 2009)
This paper explores, briefly, the non-visible aspects of adult learners, notably multi- and bi-ethnic learners. The complexity and contradiction of ascribed (publicly read) and (internally embodied) felt ethnic identities comes under exploration.